Heuristic Global Optimization Algorithm for Estimating a Radio Source Location by a Passive Radar System - Ya. Shevgunov, Timofey; Vavilova, Zhanna A; Guschina, Oksana A; N. Efimov, Evgeny (TEM Journal, 2020)
The methods for generating estimator for radio source location based on digital processing of signals received at various points in space are one of the main areas of multi-position radar systems’ research. Nowadays the above-mentioned methods that can provide the highest accuracy among the others are subject of interest. So, the mean square error usually serves as a measure of accuracy, which allows formulating a convenient, for mathematical transformations, quality criteria and synthesizing the algorithms. The traditional estimation algorithms have a multi-stage character, and they are based on the formation of optimal estimators for time and phase delays of the signals and their subsequent conversion to the source coordinates. The research has the modern approaches of the development of new positioning algorithms to guarantee the achievement of the minimum mean square error and do not create excessive computing load.